Establishment of the Method of Immunoenrichment Combined with MALDI-TOF MS to Detect Cronobacter sakazakii in Milk Powder - Hong ZHAO; Liu YANG; Liangjuan ZHAO; Lu PANG; Junzhe ZHANG; Shaoying ZHU; Yuling ZHAO; Youlan TAN; Huabing ZHAO; Pei LIU; Guohong LIU; Lan WU; et al. (Shipin gongye ke-ji, 2022)
Objective: To prepare an efficient and specific antibody against Cronobacter sakazakii and its immunomagnetic beads, and establish a method of immunoenrichment combined with matrix-assisted laser desorption/ionization mass spectrometry (MALDI-TOF MS) for the detection of Cronobacter sakazakii in milk powder. Methods: The antibody and its immune beads of Cronobacter sakazakii were prepared, the capture rate of immune magnetic beads was studied in pure culture and milk powder matrix. The specific of the beads were identified and verified by using MALDI-TOF MS. Results: The capture rate of four strains of Cronobacter sakazakii and its mixed bacteria in the pure culture and milk powder matrix were all over 80%, and the results of MALDI-TOF MS showed that the identification were better under different contamination conditions of different impurities in the milk powder matrix, even under the high proportion of (1:100) of the bacteria, it could be used to identify Cronobacter sakazakii in milk powder accurately, at this time, the concentration of Cronobacter sakazakii in the sample was only 20 CFU/mL. Conclusion: A simple and accurate method for the detection of Cronobacter sakazakii in milk powder by immunoenrichment and MALDI-TOF MS was established, which provided a new method reference for the rapid and accurate identification of Cronobacter sakazakii in milk powder.